Biocontrol of Anthracnose of Black Pepper Caused by Using Mycoparasites - Anoop Sankar (Department of Plant Pathology, College of Agriculture, 2002)
An investigation was done for exploiting potential biocontrol agents for the management of anthracnose of black pepper. Survey conducted on the incidence of anthracnose disease in eleven different locations of the state during February - July 2000 revealed that Colletotrichum gloeosporioides was the most common pathogen associated with this disease. Distinct variability in morphological characters and pathogenicity was exhibited by the di"fferent isolates of the pathogen. The most virulent isolate was isolate C6 from Perinthalmanna. The pathogen survived for three months on infected leaves in the soil and upto five months on infected leaves under laboratory conditions. A study was conducted to isolate potential mycoparasites of C. gloeosporioides from the rhizosphere and phyllosphere of both healthy and diseased black pepper plants from the various locations surveyed. Among the fungi isolated, two isolates of Trichoderma harzianum Rifai (T I and T 2) and two isolates of Aspergillus niger van Tieghem (A, and A2) were found to be most effective in' inhibiting C. gloeosporioides in vitro. After mass multiplication, the selected fungal antagonists were formulated in talc, which was found to be the best carrier material for maintaining the viability of the antagonists. The shelf life of the talc based formulations were 150 days and 180 days for the T. harzianum isolates and A. niger isolates respectively. The antagonistic fungi were tested separately under greenhouse conditions by a combination of two methods of application viz., soil application and foliar spray. Greenhouse studies indicated that all the four isolates were equally